A halogenated Schiff base supramolecular dimer as a pH probe and its application
By designing a pH probe based on the haloschiff base supramolecular dimer and using halogen atoms to regulate intermolecular interactions, the problem of insufficient sensitivity and signal-to-noise ratio under slight pH environment changes in traditional fluorescent probes is solved, and a pH probe with high signal-to-noise ratio and stability is achieved, suitable for detection of pH values of 5.0-7.0.
Patent Information
- Application Number
- CN202310505221.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-06
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2043-05-06
AI Technical Summary
Traditional fluorescent probes have weak sensitivity, signal-to-noise ratio and stability under slight pH changes, and the redesign of the molecular framework will lead to a decrease in accuracy and signal-to-noise ratio.
Design and synthesize pH probes based on haloschiff base supramolecular dimers to regulate intermolecular interactions through the introduction of halogen atoms, improving signal-to-noise ratio and stability.
In the pH range of 5.0-7.0, the fluorescence intensity of Zn-Cl-L and Zn-Br-L increased by 12.2 and 6.7 times, respectively, and the signal-to-noise ratio was significantly improved, and excellent stability and reversibility were shown in this range.
Smart Images

Figure CN116554053B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of fluorescent probes, and in particular relates to a halogenated Schiff base supramolecular dimer of a high-performance pH probe and application thereof. Background Art
[0002] Using pH test paper to detect pH is a convenient and accessible method because it provides a visual color change and achieves semi-quantitative pH measurement. Among them, fluorescence detection technology is widely used and studied because of its high sensitivity, good selectivity, and ability to meet real-time response under various special conditions. So far, fluorescent probes based on mechanisms such as intramolecular charge transfer (ICT), fluorescence resonance energy transfer (FRET), and photoinduced electron transfer (PET) have been widely developed and used for pH detection.
[0003] However, the mechanism of fluorescence signal formation of most probes is based on changes in electronic structure or covalent structure, which makes the radiative transition and non-radiative transition change rate of traditional fluorescent probes relatively weak under slight changes in pH environment, which usually leads to limited sensitivity, signal-to-noise ratio and stability. In addition, the control strategy for traditional probe performance often focuses on the redesign of the probe molecular skeleton. However, changes in the molecular skeleton usually lead to fundamental changes in the mode of action, which will lead to a decrease in accuracy and signal-to-noise ratio, and even fundamental changes in probe behavior. Therefore, it is still a huge challenge to design and synthesize high-performance probes with adjustable fluorescence behavior to meet the needs of complex applications.
[0004] Supramolecular assembly is a molecular aggregate assembled by intermolecular recognition, and its physicochemical properties can be regulated by the degree of aggregation without changing the internal structure of the molecule. The driving force of supramolecular assembly is usually attributed to intermolecular interactions, such as π-π stacking, hydrogen bonding, halogen bonding, and electrostatic interactions, which can change significantly with changes in the H+ environment. Previous studies have shown that intermolecular π-π interactions are the main driving force for molecular aggregation, and halogen atoms can affect the electronic structure of the benzene ring through p-π conjugation or inductive effects. Therefore, by replacing hydrogen atoms on the benzene ring with different halogen atoms, the surface charge distribution of the benzene ring can be controlled and the strength of intermolecular interactions can be promoted. In this case, the charge transfer between fluorescent dyes becomes easier and the charge distribution is more concentrated, which leads to the weakening of electronic coupling between fluorescent dyes and the acceleration of the rate of radiative and non-radiative transitions. In addition, since the change of halogen atoms does not affect the mode of intermolecular interaction, it is theoretically feasible to control the strength of intermolecular interaction by adjusting different halogen atoms to improve the signal-to-noise ratio of the probe.
[0005] Salen-type molecules are a class of Schiff base compounds with diverse structures and properties formed by the aldol condensation reaction of different salicylaldehydes and diamines. Salen has been studied in depth for decades as an important molecule in the field of materials science. Their specific fluorescence behavior has been widely used in the field of identification, such as bioimaging, metal ion recognition, explosive detection, and environmental detection. However, due to the small change in fluorescence intensity and poor stability of salen-type compounds under different pH environments, it is difficult to use them as pH chemical sensors. Therefore, the research on salen-type pH sensors is still in its infancy, and how to improve the signal-to-noise ratio and stability of salen-type probes is the main bottleneck for further development in this field. Summary of the invention
[0006] The first object of the present invention is to provide a halogenated Schiff base supramolecular dimer as a high-performance pH probe with high sensitivity, high signal-to-noise ratio and good stability. The second object of the present invention is to provide a pH value detection test paper based on the halogenated Schiff base supramolecular dimer.
[0007] The first object of the present invention is achieved in that the halogenated Schiff base supramolecular dimer used as a pH probe is Zn-Cl-L (Zn II -3,5-Cl-saldmpn) and Zn-Br-L (Zn II -3,5-Br-saldmpn; The pH value of the two halogenated Schiff base supramolecular dimers was detected in the range of 5.0 to 7.0.
[0008] The second object of the present invention is achieved by providing a pH test paper based on the halogenated Schiff base supramolecular dimer, wherein the preparation method of the test paper is as follows: soaking the test paper in an aqueous solution of the halogenated Schiff base for 24 hours, and drying the test paper in an oven at 105 degrees Celsius for 20 minutes to obtain the test paper.
[0009] The beneficial effects of the present invention are:
[0010] 1. The halogenated Schiff base supramolecular dimer pH value detection fluorescent probe provided by the present invention shows obvious aggregation-induced quenching (ACQ) phenomenon in the range of 5.0-7.0. Compared with non-halogenated Schiff base compounds, the signal-to-noise ratio of non-halogenated Schiff base compounds is as low as 1.7 times, while the signal-to-noise ratio of the Schiff base probe based on halogen regulation of the present invention is greatly increased, and the fluorescence intensities of Zn-Cl-L and Zn-Br-L are increased by 12.2 and 6.7 times, respectively, indicating that the introduction of halogen atoms can increase the intermolecular interaction pathways and enhance the intermolecular interaction strength, thereby increasing the aggregation degree of the aggregates, resulting in drastic changes in radiative transitions and non-radiative transitions, and increasing the signal-to-noise ratio.
[0011] 2. The halogenated Schiff base supramolecular dimer provided by the present invention has excellent stability, selectivity and reversibility in a solution with a pH value of 5.0-7.0, and can be used for pH detection of a solution with a pH value of 5.0-7.0.
[0012] 3. This invention has explored in detail the possible mechanism of different signal-to-noise ratios caused by substitution of different atoms (Cl, Br, H) through single crystal structure analysis and theoretical calculations. This provides new ideas and directions for the design and development of high-performance fluorescent probes. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 a, b, and c are FT-IR spectra of Zn-Cl-L, Zn-Br-L, and Zn-L in the present invention, respectively;
[0014] Figure 2 a and b are the emission spectra of Zn-Cl-L and Zn-Br-L at different pH values (Zn-Cl-L: λex = 380 nm; Zn-Br-L: λex = 370 nm); Figure 2 c and d are the linear relationships between the fluorescence intensity of Zn-Cl-L and Zn-Br-L and pH value (5.0-7.0), respectively; Figure 2 e and f are the fluorescence photos of Zn-Cl-L and Zn-Br-L at different pH values (5.0-7.0) under 365nm ultraviolet light;
[0015] Figure 3 is the ratio of the fluorescence intensity of Zn-Cl-L, Zn-Br-L and Zn-L when the pH changes from 5.0 to 7.0 in ethanol solution;
[0016] Figure 4 Where a and b are the pKa values of Zn-Cl-L and Zn-Br-L respectively;
[0017] Figure 5 a, b, and c are the emission spectra of Zn-Cl-L, Zn-Br-L, and Zn-L at different pH values (2.0-12.0), respectively; Figure 5 Figures d, e, and f are the linear relationships between the fluorescence intensity of Zn-Cl-L, Zn-Br-L, and Zn-L and pH values (2.0-12.0), respectively;
[0018] Figure 6 a, b, and c are the absorption spectra of Zn-Cl-L, Zn-Br-L, and Zn-L at different pH values (5.0–7.0), respectively (Inset: photos at pH 5.0 and 7.0 under natural light);
[0019] Figure 7a and b are the stability changes of Zn-Cl-L and Zn-Br-L at different pH values (5.0 and 7.0) for 15 days, respectively (Inset: color changes at pH 5.0 and 7.0 after 15 days under natural light); Figure 7 Figure c is the stability change diagram of Zn-L at pH 5.0 and 7.0 for 7 days (color change at pH 5.0 and 7.0 after 7 days under natural light); Figure 7 d and e are the interference experimental results of different metal ions and anions on Zn-Cl-L (inset: the corresponding fluorescence photos of Figures d and e);
[0020] Figure 8 Figure a shows the interference experiment results of different metal ions on Zn-Br-L (the inset is the corresponding fluorescence photo). Figure 8 Figure b shows the interference experiment results of different anions on Zn-Br-L (the inset is the corresponding fluorescence photo);
[0021] Fig. 9 a and b are schematic diagrams of the reversible responses of Zn-Cl-L and Zn-L, respectively; Fig. 9 c is the reversible response of Zn-Cl-L between acidic and alkaline conditions (blue channel extracted from the image);
[0022] Fig.10 a is a schematic diagram of the reversible response of Zn-Br-L; Fig.10 b and c are the reversible responses of Zn-Br-L and Zn-L between acidity and alkalinity, respectively (blue channel extracted from the image);
[0023] Fig.11 The photos show the fluorescence color changes of Zn-Cl-L test paper in response to different pH values (5.0-7.0);
[0024] Fig.12 is the linear relationship between the blue channel and different pH values;
[0025] Fig.13 a, b, and c are the absolute quantum yields (QY) of Zn-Cl-L at pH 5.0, 6.0, and 7.0, respectively;
[0026] Fig.14 a, b, and c are the absolute quantum yields (QY) of Zn-Br-L at pH 5.0, 6.0, and 7.0, respectively;
[0027] Fig.15 a, b, and c are the absolute quantum yields (QY) of Zn-L at pH 5.0, 6.0, and 7.0, respectively;
[0028] Fig.16a, b, and c are schematic diagrams of the fluorescence lifetimes of Zn-Cl-L, Zn-Br-L, and Zn-L at different pH values (5.0-7.0);
[0029] Fig.17 a in the figure shows the powder images of Zn-Cl-L, Zn-Br-L and Zn-L under sunlight and ultraviolet light; Fig.17 Middle b is a schematic diagram of aggregation-induced quenching (ACQ); Fig.17 c and d are the particle size distributions of Zn-Cl-L and Zn-L at different pH values (7.0, 6.0, and 5.0) measured by dynamic light scattering (DLS); Fig.17 e and f are SEM images of Zn-Cl-L and Zn-L at different pH values (7.0, 6.0 and 5.0), respectively;
[0030] Fig.18 The particle size distribution of Zn-Br-L at different pH values (7.0-5.0) was measured by dynamic light scattering (DLS);
[0031] Fig.19 a, b, and c are Tyndall effect diagrams of Zn-Cl-L, Zn-Br-L, and Zn-L at different pH values (5.0-7.0), respectively;
[0032] Fig. 20 The SEM images of Zn-Br-L at different pH values (7.0-5.0);
[0033] Fig.21 a is the dimer aggregate supramolecular {[Zn II Ball-and-stick schematic diagram of -3,5-Cl-saldmpn]2}(Zn-Cl-L); Fig.21 b is the coordination environment of Zn(1) and Zn(2) centers shown as a polyhedron; Fig.21 c, d, and e are the enlarged regions of multiple intermolecular interactions between Zn (1) and Zn (2);
[0034] Fig. 22 a, b, and c are the molecular orbital surfaces of HOMO and LUMO of Zn-Cl-L, Zn-Br-L, and Zn-L at the b3lyp / 6-311+g (d, p) level, respectively; Fig. 22 Figures d, e, and f are schematic diagrams of the binding energy of Zn-Cl-L, Zn-Br-L, and Zn-L supramolecular dimer, respectively. DETAILED DESCRIPTION
[0035] The present invention will be further described in detail below in conjunction with the accompanying drawings and embodiments, but the present invention is not limited in any way. Any changes or improvements made based on the teachings of the present invention fall within the protection scope of the present invention.
[0036] The present invention provides a halogenated Schiff base supramolecular dimer as a pH probe, which is Zn-Cl-L (Zn II -3,5-Cl-saldmpn)(Zn-Br-L(Zn II -3,5-Br-saldmpn; its pH detection range is 5.0 to 7.0.
[0037] When the pH value of the aqueous solution of the two halogenated Schiff base supramolecular dimers increases from 5.0 to 7.0, the fluorescence intensity is linearly enhanced by 12.2 and 6.7 times, respectively; the pKa values of the two halogenated Schiff base supramolecular dimers are 6.05 and 6.11, respectively; the fluorescence intensity of the halogenated Schiff base supramolecular dimer in a solution with a pH value of 5.0-7.0 can be stably maintained for more than 15 days, and the number of reversible responses to pH is more than 20 times.
[0038] The fluorescence intensity of the halogenated Schiff base supramolecular dimer can be stably maintained for more than 15 days under the condition of pH 5.0-7.0, and the number of reversible responses to pH is more than 20 times.
[0039] The reversible response of the halogenated Schiff base supramolecular dimer to pH means that the fluorescence of the aqueous solution of the halogenated Schiff base supramolecular dimer is quenched after the addition of HCl aqueous solution, and the fluorescence is restored after the addition of NaOH aqueous solution, and the cycle process can be repeated more than 20 times.
[0040] The concentration of HCl and NaOH aqueous solutions is 1×10 5 µM.
[0041] The concentration of the aqueous solution of the halogenated Schiff base supramolecular dimer is 40-400 μM.
[0042] The invention also provides a pH value detection test paper based on the halogenated Schiff base supramolecular dimer.
[0043] The preparation method of the test paper is as follows: after the test paper is immersed in the aqueous solution of the halogenated Schiff base for 24 hours, it is dried in an oven at 105 degrees Celsius for 20 minutes to obtain the test paper.
[0044] During the test, the volume of the solution to be tested is 1-10 μL.
[0045] The present invention further provides a method for detecting pH value using a mobile phone based on the pH value detection test paper. The method uses an external high-definition camera and built-in application software of the mobile phone to extract RGB parameters on the test paper, and accurately calculates the pH value of the unknown solution from the blue (B) numerical channel through an imaging system using a fitting formula.
[0046] Example 1
[0047]
[0048] Formula (I)
[0049] Weigh 0.191g (1.0mmol) 3,5-dichlorosalicylaldehyde and 82μL (0.5mmol) N,N-bis(3-aminopropyl)methylamine, dissolve in 50ml ethanol solution, and stir at room temperature for 2 hours. Then add 0.069g (0.5mmol) ZnCl2 to the above mixture, and then stir the resulting yellow solution for 1 hour and filter. After standing at room temperature for three days, yellow transparent Zn-Cl-L crystals are obtained. The crystalline product is washed with ethanol and air-dried (yield 72.6%). FT-IR (KBr, cm-1): 1631 (C=N), 1450 (CH3), 1162 (CO), 864 (Zn-N), 758 (C-Cl), 557 (Zn-O) ( Figure 1 a). The reaction formula is shown in formula (I).
[0050] Example 2
[0051]
[0052] Formula (II)
[0053] Weigh 0.280g (1.0mmol) 3,5-dibromosalicylaldehyde and 82μL (0.5mmol) N,N-bis(3-aminopropyl)methylamine, dissolve in 50ml ethanol solution, and stir at room temperature for 2 hours. Then add 0.069g (0.5mmol) ZnCl2 to the above mixture, and then stir the resulting yellow solution for 1 hour and filter. After standing at room temperature for three days, yellow transparent Zn-Br-L crystals are obtained. The crystalline product is washed with ethanol and air-dried (yield 71.8%). FT-IR (KBr, cm-1): 1631 (C=N), 1446 (CH3), 1149 (CO), 871 (Zn-N), 702 (C-Br), 553 (Zn-O) ( Figure 1 b). The reaction formula is shown in formula (II).
[0054] Example 3
[0055]
[0056] Formula (III)
[0057] Weigh 0.125g (1.0mmol) salicylaldehyde and 82μL (0.5mmol) N,N-bis(3-aminopropyl)methylamine, dissolve in 50ml ethanol solution, and stir at room temperature for 2 hours. Then add 0.069g (0.5mmol) ZnCl2 to the above mixture, and then stir the resulting yellow solution for 1 hour and filter. After standing at room temperature for three days, yellow transparent Zn-L crystals are obtained. The crystalline product is washed with ethanol and air-dried (yield 64.5%). FT-IR (KBr, cm-1): 1627 (C=N), 1473 (CH3), 1153 (CO), 899 (Zn-N), 758 (CH), 597 (Zn-O) ( Figure 1 c). The reaction formula is shown in formula (III).
[0058] Example 4 Preparation and detection of fluorescent sensor test paper
[0059] A circular test paper with a radius of 4 cm was immersed in a solution with a concentration of 1×10 -2 mmol / mL Zn-Cl-L solution for one day to ensure that the solute can be absorbed to the surface and evenly dispersed in the pores of the test paper. Then, it was taken out with tweezers, put into a beaker, and dried in an oven at 105 °C for 20 min to obtain the fluorescent sensing test paper. The prepared test paper was placed under a 365nm UV lamp and then ethanol solutions (5μL) with different pH values (5.0-7.0) were dropped into it. The test papers were visually observed in the dark.
[0060] The experimental results show that ( Fig.11 ), as the pH increases, the fluorescence gradually changes from black weak fluorescence to blue strong fluorescence, and the fluorescence intensity increases significantly, which is closely related to the pH value of the solution to be tested ( Fig.11 ).
[0061] Example 5: pH value detection using mobile phone
[0062] Although the test strip can be detected by visual colorimetry, this method relies on the human ability to discern small color changes, so its accuracy and sensitivity need to be further improved. This embodiment uses a mobile phone imaging system and extracts RGB values through a color analysis application. These values are plotted together with the pH value, and it is found that as the pH value increases, the color gradually changes from black to blue, resulting in a significant increase in the blue complementary color, so that the pH value can be quantitatively calculated.
[0063] This example uses the blue channel for slope fitting and calculates R 2 is 0.998 ( Fig.12). The pH value of the unknown solution can be accurately calculated by this fitting formula and can be calculated from the blue channel value by the imaging system.
[0064] Test Example 1
[0065] Detection of photophysical properties of halogenated Schiff base supramolecular dimers of the present invention
[0066] 1. Fluorescence intensity changes of the halogenated Schiff base supramolecular dimer of the present invention at different pH values
[0067] Methods: Ethanol solutions of HCl and NaOH with different concentrations were added to Zn-Cl-L (c=400µM) solution. The fluorescence emission spectra of the solutions were measured at each pH unit (2.0-12.0) (Zn-Cl-L: λex=380nm; Zn-Br-L: λex=370nm; Zn-L: λex=355nm).
[0068] Results: As the pH changes from 2.0 to 5.0, the overall fluorescence intensity does not change much, showing fluorescence quenching. In contrast, when the pH changes from 7.0 to 12.0, the fluorescence emission is stronger, but there is still no significant fluctuation. When the pH changes from 5.0 to 7.0, the fluorescence intensity of the two halogenated Schiff base supramolecular dimers of the present invention increases sharply ( Figure 2 Among them, the fluorescence intensity of Zn-Cl-L and Zn-Br-L increased by 12.2 and 6.7 times, respectively ( Figure 3 ), and they all show very good linearity in this range ( Figure 2 (c, d), R 2 The pKa values of Zn-Cl-L and Zn-Br-L were 0.996 and 0.990, respectively. Then, the pKa values of Zn-Cl-L and Zn-Br-L were calculated to be 6.05 and 6.11, respectively ( Figure 4 ).
[0069] The fluorescence intensity change of the solution when the pH value decreased from 7.0 to 5.0 was observed under 365nm UV light ( Figure 2 (e, f) This is exactly the same as the measured result, and the relevant changes can be observed directly with the naked eye.
[0070] The coordination complex is stable within a certain pH range, especially the pH value of its synthesis environment (Zn-Cl-L: pH = 5.8; Zn-Br-L: pH = 5.7). This fluorescence behavior with a very high signal-to-noise ratio in a very small pH range is very rare. Compared with the non-halogenated Schiff base complex Zn-L ( Figure 5In (c, f), although the fluorescence of Zn-L also increased as the pH value changed from 5.0 to 7.0, its signal-to-noise ratio was very low, only 1.7.
[0071] 2. The ultraviolet absorption spectrum of the halogenated Schiff base supramolecular dimer of the present invention is as follows: Figure 6 , as the pH dropped from 7.0 to 5.0, the absorption peak of Zn-Cl-L at 380nm gradually decreased, and a new absorption peak gradually formed at 345nm. Similar to Zn-Cl-L, the ultraviolet absorption spectrum of Zn-Br-L also showed different degrees of blue shift, and the disappearance and new formation of absorption peaks were at 383nm and 341nm, respectively. The absorption peak intensity of Zn-L at 352nm gradually weakened, and no new absorption peak was observed. In addition, with the increase of acidity, it can be clearly observed under fluorescent light that the color of Zn-Cl-L and Zn-Br-L changed from colorless to yellow, while Zn-L did not have a similar phenomenon ( Figure 6 Thus, the halogen-mediated Schiff base probe can be used as a “naked-eye” colorimetric indicator of acidic pH.
[0072] 3. Stability test method: The stability of the two halogenated Schiff base supramolecular dimers was evaluated by measuring the changes in fluorescence intensity at different time points. The halogenated Schiff base supramolecular dimer solution with a concentration of 400µM was sealed and placed under natural conditions, and the fluorescence intensity was measured every 1 day for 15 days.
[0073] Results: From Figure 7 It can be seen that under the condition of pH 7.0, the fluorescence intensity of Zn-Cl-L and Zn-Br-L is very stable. Although the fluorescence intensity of the two probes is relatively low under the condition of pH 5.0, the fluorescence intensity remains stable after 15 days. However, the experimental results of the reference substance Zn-L are not satisfactory ( Figure 7 c). Under pH 7.0, the fluorescence intensity began to decrease after only 4 days. Under acidic conditions (pH=5.0), the fluorescence decreased on the second day. After 7 days, the fluorescence intensity of pH 7.0 and 5.0 decreased to almost the same extent, and solid precipitates appeared in the solution ( Figure 7 This indicates that Zn-L may have decomposed and is less stable.
[0074] Comprehensive experimental results show that the supramolecular dimer probe regulated by halogen exhibits good stability and is expected to play an important role in practical applications.
[0075] 4. Selective detection
[0076] The selectivity of the probes was evaluated by detecting the fluorescence responses of Zn-Cl-L and Zn-Br-L to some other substances, including common metal ions and anions.
[0077] Method: First, the prepared Zn-Cl-L and Zn-Br-L solutions were diluted to 400µM and shaken at room temperature for 10 seconds to ensure adequate mixing. Then different types of interfering substances were added, mixed with Zn-Cl-L and Zn-Br-L, and the fluorescence spectra were immediately measured. (Zn-Cl-L: λex=380nm; Zn-Br-L: λex=370nm).
[0078] The results are as follows Figure 7 In d, e and Figure 8 As shown in the figure, in the presence of the above substances, the fluorescence spectra of Zn-Cl-L and Zn-Br-L are almost constant. In sharp contrast, when the pH changes to 5, the fluorescence intensity of Zn-Cl-L and Zn-Br-L decreases significantly. These results indicate that the halogen-regulated Schiff base probe is only sensitive to pH but is not affected by common interfering substances.
[0079] 5. Reversibility test
[0080] In order to achieve real-time and accurate monitoring of pH changes, the reversible response of pH is an important characteristic. This detection example detects the fluorescence intensity of Zn-Cl-L and Zn-Br-L under acidic and alkaline conditions.
[0081] Methods: First, the prepared Zn-Cl-L and Zn-Br-L solutions were diluted to 400 µM and shaken at room temperature for 10 seconds to ensure thorough mixing. 5 µM) and NaOH (1×10 5 The pH value of the aqueous solution was adjusted between acidic and alkaline, and the change of fluorescence intensity was observed.
[0082] The experimental results show that ( Fig. 9 In a), Zn-Cl-L exhibits high fluorescence at pH=7.0. When an acidic buffer solution is added, the fluorescence is quenched, but after an alkaline buffer solution is added, the fluorescence is significantly restored. The reversible change in fluorescence intensity can be repeated more than 20 times ( Fig. 9 Meanwhile, Zn-Br-L exhibited a similar phenomenon ( Fig.10 However, due to the extremely low signal-to-noise ratio and poor stability of Zn-L, we were unable to observe a similar reversible phenomenon ( Fig. 9 (b, c).
[0083] The above experimental results show that the Schiff base probe based on halogen regulation of the present invention has excellent reversible response performance and can realize real-time and accurate monitoring of pH changes.
[0084] Experimental Example 1 Study on the sensing mechanism of two halogenated Schiff base supramolecular dimers of the present invention
[0085] 1. In order to study the special optical behavior of halogenated Schiff base supramolecular dimers, the quantum yield and fluorescence lifetime were measured and the results were compared with those of non-halogenated Schiff base complexes.
[0086] Fig.13 The quantum yield of Zn-Cl-L at different pH values is shown in Figure 2. When the pH value decreases from 7.0 to 5.0, the quantum yield of Zn-Cl-L decreases significantly from 19.4% to 4.4%. Similar to Zn-Cl-L, the quantum yield of Zn-Br-L also decreases by 2.7% ( Fig.14 ). The quantum yield of Zn-L only decreased significantly when the pH dropped from 6.0 to 5.0, falling to 5.6% ( Fig.15 ). Fluorescence lifetime ( Fig.16), the fluorescence lifetimes of Zn-Cl-L and Zn-Br-L also decreased with decreasing pH values, decreasing by 4.03ns and 0.16ns, respectively. The fluorescence lifetime of Zn-L hardly changed when the pH value dropped from 7.0 to 6.0, but it dropped significantly to 1.29ns when the pH value dropped to 5.0. We then used the quantum yield and fluorescence lifetime to calculate the radiative decay rate constant (kr) and non-radiative decay rate constant (knr) of the three Schiff base complexes (Table 1). It can be seen that as the pH value dropped from 7.0 to 5.0, the kr of Zn-Cl-L and Zn-Br-L both decreased, and the knr both increased, which means that the transmission efficiency of the emitted light will decrease because the energy of the excitation light will be more easily dispersed into other forms of energy for transmission. It is worth noting that under the same pH conditions, the knr of Zn-Br-L is much greater than that of Zn-Cl-L, which may be caused by the heavy atom effect. Specifically, the heavy atom effect causes the compression of electron orbits and the movement of energy levels, which leads to an increase in the average velocity of electrons, thereby increasing the interaction strength between electrons and the lattice. The enhancement of this interaction leads to an increase in the non-radiative transition rate constant, which manifests as a decrease or quenching of fluorescence. The heavy atom effect may reduce the signal-to-noise ratio of Zn-Br-L at different pH to some extent. Interestingly, when the pH decreases from 7.0 to 6.0, the kr value of Zn-L increases, indicating that the transmission of its emitted light becomes easier, which is consistent with the fluorescence enhancement phenomenon observed previously. However, as the pH continues to decrease to 5.0, the kr value begins to decrease, while the knr value increases. This tortuous change greatly limits the signal-to-noise ratio of Zn-L. In addition, the knr of the three Schiff base complexes is much higher than the kr, indicating that the intermolecular interaction has an important influence on their fluorescence behavior.
[0087] Literature shows that molecular interactions can utilize H + As a driving force to construct specific supramolecular aggregates. The formation of such aggregates will lead to a significant decrease in the radiative decay rate constant kr, because the intermolecular interaction will inhibit the emission process. At the same time, the excited state of the aggregate usually decays through a non-radiative pathway, which will lead to a significant increase in the non-radiative decay rate constant knr. In addition, according to the exciton theory, the dye molecule can be regarded as a point dipole, and the exciton state of the aggregate is split into two energy levels through the interaction of the transition dipole. When any two dipoles in the aggregate are parallel, the repulsive force between them will lead to a higher energy state, causing the ultraviolet absorption spectrum to blue shift. This is exactly the same as the phenomenon observed previously. Based on the above, it can be inferred that the special fluorescence behavior of different signal-to-noise ratios exhibited by different Schiff base supramolecular dimers may be related to the formation of aggregates.
[0088] Table 1 Photophysical parameters of Zn-Cl-L, Zn-Br-L and Zn-L
[0089]
[0090] Note: Φ f = fluorescence quantum yield, τ f = fluorescence lifetime, k r =Φ f / τ f = radiative decay rate constant, k nr =(1-Φ f ) / τ f = non-radiative decay rate constant
[0091] 2. In order to explore the effect of aggregation state on the fluorescence intensity of Schiff base complex compounds, this experimental example observed the fluorescence performance of three Schiff base complex solids under 365nm ultraviolet light.
[0092] The results show that ( Fig.17 In figure a), although these three Schiff base complexes all emit yellow light under sunlight, they all show fluorescence quenching under 365nm ultraviolet light. This is due to the formation of Schiff base complex molecular aggregates, which causes non-radiative transitions and thus causes the fluorescence Schiff base complex quenching. This is consistent with the increase in the non-radiative decay rate constant mentioned above. This is a typical aggregation-induced quenching (ACQ) behavior ( Fig.17 (b)
[0093] 3. In order to study the effect of aggregation degree on fluorescence signal-to-noise ratio, the present invention conducted a dynamic light scattering (DLS) experiment and observed the changes in the Tyndall phenomenon of the three Schiff base complexes at different pH values.
[0094] The experimental results show that ( Fig.17 c and 18), as the pH dropped from 7.0 to 6.0, the particle sizes of the halogen-substituted Schiff base complexes Zn-Cl-L and Zn-Br-L increased to varying degrees, increasing by 162.7nm and 117.6nm, respectively. As the pH further decreased, the particle sizes of Zn-Cl-L and Zn-Br-L continued to increase, reaching an astonishing 292.4nm and 262.4nm, respectively. In comparison, the particle size of the traditional Schiff base complex Zn-L barely changed as the pH dropped from 7.0 to 6.0, but when the pH dropped to 5.0, the particle size of Zn-L suddenly increased to 111.6nm ( Fig.17 At the same time, we observed that as the pH decreased from 7.0 to 5.0, the halogenated Schiff base supramolecular dimer gradually showed the Tyndall phenomenon ( Fig.19a, b), and showed a strong Tyndall phenomenon at pH 5.0. However, the traditional Schiff base complex Zn-L only showed a weak Tyndall phenomenon at pH 5.0 ( Fig.19 (c). It is well known that the Tyndall effect reflects the size of nanoparticles in solution to a certain extent. The stronger the Tyndall effect, the larger the nanoparticles. This is consistent with the DLS data.
[0095] 4. Scanning electron microscopy (SEM) was used to observe the self-assembly pathways of the three Schiff base complexes at the microscopic level.
[0096] At pH 7.0, the three Schiff base complexes exhibited a dispersed granular structure ( Fig.17 Zhongehe Fig. 20 ). However, when the pH dropped to 6.0, the halogenated Schiff bases began to aggregate and formed smaller clusters. When the pH continued to drop to 5.0, Zn-Cl-L and Zn-Br-L formed a cotton-like aggregate. However, in contrast, the structure of Zn-L hardly changed during the process of pH dropping from 7.0 to 5.0, and only when the pH reached 5.0 did it appear in a block-like aggregate form ( Fig.17 (middle f).
[0097] The results show that the substitution of halogen atoms can effectively increase the degree of aggregation between molecules, and the formation of aggregates is usually driven by the interaction of π-π stacking. In the case of π-π stacking, the distance between molecules is very close, so the electronic interaction between molecules becomes stronger. This interaction can lead to a decrease in the radiative transition constant, because radiative transition requires molecules to absorb photons and transfer electrons from one energy level to another. When the distance between molecules is very close, the electronic energy level structure of the molecule becomes more complicated, so radiative transition becomes more difficult. On the other hand, π-π stacking can also lead to an increase in the non-radiative transition constant. Non-radiative transition refers to the transition of electrons from one energy level to another, but no photons are emitted. In the case of π-π stacking, the interaction between molecules can lead to an increase in the rate of non-radiative transitions because the electron transfer between molecules becomes easier. This situation may lead to the fluorescence quenching of the molecule, thereby weakening the fluorescence intensity of the molecule. As the pH decreases, the formation of aggregated states leads to a decrease in the radiative transition constant of the halogenated Schiff base and an increase in the non-radiative transition constant, resulting in Zn-Cl-L and Zn-Br-L having an extremely high signal-to-noise ratio. However, the heavy atom effect forces the non-radiative transition constant of Zn-Br-L to be much larger than that of Zn-Cl-L, which makes its signal-to-noise ratio slightly lower than that of Zn-Cl-L in a limited pH range. In contrast, since Zn-L is not substituted by halogen atoms, it is more difficult to produce an aggregated state, and the changes in the alkali radiative transition constant and the non-alkali radiative transition constant are not large, resulting in a much lower signal-to-noise ratio than that of halogenated Schiff bases.
[0098] 5. Structure and theoretical calculation
[0099] Although the fluorescence behavior of the reported compounds comes from the intermolecular interactions in the solution environment, their solid-state aggregation is crucial for understanding the corresponding mechanism. Therefore, in order to obtain structural information in the form of single crystals, this experimental example uses anhydrous ethanol as the solvent, and the halogenated ligand H2saldmpn (H2-χ-L) reacts with zinc chloride in a stoichiometric ratio of 1:1. After one week, colorless crystals suitable for single crystal diffraction are crystallized. X-ray structural analysis shows that Zn-χ-L crystallizes in the monoclinic system (space group P21 / c). Surprisingly, the asymmetric unit includes two crystallographically independent neutral Zn-χ-L (abbreviated as [Zn1] and [Zn2]) units with exactly the same composition ( Fig.21(a) According to the search results of Cambridge Crystallographic Database (CSD), although some non-halogen derivatives of saldmpn can be found in the database, all the structures found exist in the form of isolated single molecules. In addition to a previously reported halogenated trimer that also uses a halogenated Schiff base as a ligand, the Zn-χ-L series of compounds (Zn-Cl-saldmpn and Zn-Br-saldmpn) is the second supramolecular polymer based on saldmpn constructed by the same unit. From the objective experimental results, the substitution of halogen atoms is conducive to the formation of supramolecular polymers.
[0100] like Fig.21 As shown in (b), each saldmpn2- acts as a five-fold ligand to provide {N3O2} coordination for the central atom, namely, one amine (Nam) and two imino nitrogen atoms (Nim) and two phenolic oxygen atoms O*. The longest bond length around the metal center is the Zn-Nam bond, ranging from 1.960 to 2.196Å, with the Zn-Nam bond being the longest (2.149-2.196Å), the Zn-Nim bond being slightly shorter than that of Zn-Nam (2.049-2.087Å), and the Zn-O* bond being the shortest (1.960-2.00Å). The lengths of these characteristic bonds of the studied Zn-χ-L are all within the normal range of previously reported saldmpn-type zinc complexes. It is worth noting that since the central atom adopts a five-fold coordination mode with the saldmpn2- ligand, there are two possibilities for its geometry: square pyramid (tetragonal pyramid SP) and trigonal bipyramid (TB), and these two coordination geometries can be well determined by the Addison parameter τ. From the calculation results, we can see that the τ values of the four zinc atoms in the two compounds show certain differences ( Figure 6 (b) The values of τ of Zn1 and Zn2 in Zn-Cl-saldmpn are (τ1=0.738, τ2=0.828), while those of Zn1 and Zn2 in Zn-Br-saldmpn are (τ1=0.7165, τ2=0.805), respectively. These data indicate that the four zinc atoms have the same geometric shapes and belong to the SP configuration.
[0101] The results of the analysis of intramolecular and intermolecular weak interactions show that in addition to the classical hydrogen bond interactions, a variety of other intermolecular interactions are formed in the dimer, including halogen bonds, π bonds, etc. As shown in the figure, the two molecules can be divided into three parts from left to right to left. The first part is the strong double CH...O (C27-H27...O2, C28-H28...O2), the second part is the π-π interaction [Cg1..Cg2] ((Cg1:C1-C2-C3-C4-C5-C6; (Cg2:C1-C2-C3-C4-C5-C6)) in the middle of the two molecules; the third part is the halogen bond CH--Cl and CH...O. Due to the synergistic effect of these weak interactions, the two neutral molecules are connected to each other to form a unique dimeric supramolecular polymer. In addition, the CH...Cl interaction connects the adjacent dimeric supramolecular polymers into a one-dimensional chain, such as Figure 7 shown.
[0102] 6. In order to better explain the chemical reactivity, electrical structure and optical properties of the reported compounds, this experimental example used density functional theory (DFT) for theoretical calculations, using the B3LYP function level of the 6-311g (d, p) basis set. It should be pointed out that the experimental results show that the fluorescence intensity at pH = 7 mainly comes from a single molecule, so in this experimental example, the atomic coordinates used for optimization come from the crystal structure of the Zn1 fragment. In addition, in order to reveal the influence of halogen atoms on fluorescence behavior, this experimental example introduced the non-halogen isomer Zn-L for comparison. Fig.21 As shown, the optimized geometry of the Zn1 fragment is in good agreement with the crystal data. The good agreement between the optimized structure and the crystal structure indicates that Zn-χ-L has good stability and rigidity. The electron cloud of Zn-χ-L at the HOMO level is distributed throughout the molecule, while the LUMO electron cloud is mainly concentrated in the introduced diphenylamine part, indicating a certain degree of charge conversion. In addition, due to the introduction of halogen atoms, the electron cloud on the conjugated plane of the benzene ring of Zn-χ-L has a larger distribution area, and significantly improves the conjugation of the molecule, increases the interaction between molecules, and tends to interact with the π plane of other nearby molecules, resulting in the formation of more non-radiative paths. In contrast, the conjugated plane of the non-halogenated isomer is smaller, and the rigidity of the entire molecule leads to a more obvious steric effect, limiting the potential non-radiative paths between adjacent molecules. On the other hand, compared with Zn-L, the LUMO energy levels of Zn-Cl-L and Zn-Br-L decreased from -1.4376 to -2.143 and -1.885 eV, respectively, indicating that the substitution of halogen atoms is also beneficial to the electron acceptance ability of the Saldmpn type complex. On the other hand, the energy gaps of Zn-Cl-L and Zn-Br-L are smaller than those of Zn-L by 0.110 and 0.134 eV, respectively ( Fig. 22 From an energy perspective, the lower band gap favors the process of electron input to the LUMO and electron extraction from the HOMO. These results imply that the halide Zn-χ-L has a higher chemical reactivity than Zn-L.
[0103] 7. In order to measure the dimer energy more accurately, this experiment uses Gaussian software to calculate the interaction energy of the dimer ( Fig. 22 d~f), and the non-halogenated isostructural ...
[0104] The results show that the energies of the three compounds are ΔE1=-93.16kJ / mol (Zn-Cl-L), ΔE2=-100.56kJ / mol, and ΔE3=-56.15, respectively. It can be seen that the dimer energy of the halogenated compound is significantly higher than the compound energy. The results show that halogen atom substitution can change the arrangement pattern of molecules and increase the interaction energy between adjacent molecules. At the same time, combined with the previous experimental results, a higher interaction may mean that a stronger and more "long-range" interaction process will be formed between molecules, which will not only significantly increase the degree of molecular aggregation, but also form a wider range of responses to changes in the external environment.
Claims
1. An application of a halogenated Schiff base supramolecular dimer in preparing a pH probe with a measurement range of 5.0 to 7.0, characterized in that: The halogenated Schiff base supramolecular dimer is {[Zn II -3,5-Cl-saldmpn]2} or {[Zn II -3,5-Br-saldmpn]2}; where: The {[Zn II -3,5-Cl-saldmpn]2}, 3,5-Cl-saldmpn = N,N'-bis(3,5-dichlorosalicylaldehyde) -N,N'-bis(3-aminopropyl)methylamine, belongs to the monoclinic system, P21 / c space group, each saldmpn2- as a five-fold ligand with the central atom Zn II Provides {N3O2} coordination, namely, one amine Nam, two imino nitrogen atoms Nim and two phenol oxygen atoms O*; {[Zn II The asymmetric unit of the 2-(3,5-Cl-saldmpn)-2} consists of two crystallographically independent neutral Zn II -3,5-Cl-saldmpn units and the composition is exactly the same, the geometric configurations of its Zn1 and Zn2 units are both tetrahedral SP configurations with τ1=0.738 and τ2=0.828; The {[Zn II -3,5-Br-saldmpn]2}, 3,5-Br-saldmpn = N,N'-bis(3,5-dibromosalicylaldehyde) -N,N'-bis(3-aminopropyl)methylamine, belongs to the monoclinic system, P21 / c space group, each saldmpn2- as a five-fold ligand with the central atom Zn II Provides {N3O2} coordination, namely, one amine Nam, two imino nitrogen atoms Nim and two phenol oxygen atoms O*; {[Zn II The asymmetric unit of the 2-3,5-Br-saldmpn]2} consists of two crystallographically independent neutral Zn II -3,5-Br-saldmpn and the composition is exactly the same. The geometric configurations of its Zn1 and Zn2 units are both tetrahedral SP configurations with τ1=0.7165 and τ2=0.
805.
2. The use according to claim 1, characterized in that: A pH value detection test paper is prepared based on the halogenated Schiff base supramolecular dimer. The preparation method is as follows: after the test paper is immersed in the aqueous solution of the halogenated Schiff base for 24 hours, it is dried in an oven at 105° C. for 20 minutes to obtain the detection test paper.
3. The use according to claim 2, characterized in that: When using pH test paper for testing, the volume of the solution to be tested is 1~10μL.
4. The use according to claim 2, characterized in that: When the pH value detection test strip uses a mobile phone to detect the pH value, the external high-definition camera of the mobile phone and the built-in application software are used to extract the RGB parameters on the pH value detection test strip, and the pH value of the unknown solution is accurately calculated from the blue value channel through the imaging system through a fitting formula.
Citation Information
Patent Citations
Saldmpn type nickel halide (II) complex as well as preparation method and application thereof
CN113461741A